Hepatobiliary phenotypes of adults with alpha-1 antitrypsin deficiency. Issue 2 (25th February 2021) - Fromme, Malin; Schneider, Carolin V; Pereira, Vitor; Hamesch, Karim; Pons, Monica; Reichert, Matthias C; Benini, Federica; Ellis, Paul; H Thorhauge, Katrine; Mandorfer, Mattias; Burbaum, Barbara; Woditsch, Vivien; et al.
Abstract : Objective: Alpha-1 antitrypsin deficiency (AATD) is a common, potentially lethal inborn disorder caused by mutations in alpha-1 antitrypsin (AAT). Homozygosity for the 'Pi*Z' variant of AAT (Pi*ZZ genotype) causes lung and liver disease, whereas heterozygous 'Pi*Z' carriage (Pi*MZ genotype) predisposes to gallstones and liver fibrosis. The clinical significance of the more common 'Pi*S' variant remains largely undefined and no robust data exist on the prevalence of liver tumours in AATD. Design: Baseline phenotypes of AATD individuals and non-carriers were analysed in 482 380 participants in the UK Biobank. 1104 participants of a multinational cohort (586 Pi*ZZ, 239 Pi*SZ, 279 non-carriers) underwent a comprehensive clinical assessment. Associations were adjusted for age, sex, body mass index, diabetes and alcohol consumption. Results: Among UK Biobank participants, Pi*ZZ individuals displayed the highest liver enzyme values, the highest occurrence of liver fibrosis/cirrhosis (adjusted OR (aOR)=21.7 (8.8–53.7)) and primary liver cancer (aOR=44.5 (10.8–183.6)). Subjects with Pi*MZ genotype had slightly elevated liver enzymes and moderately increased odds for liver fibrosis/cirrhosis (aOR=1.7 (1.2–2.2)) and cholelithiasis (aOR=1.3 (1.2–1.4)). Individuals with homozygous Pi*S mutation (Pi*SS genotype) harboured minimally elevated alanine aminotransferase values, but no other hepatobiliary abnormalities. Pi*SZ participants displayed higher liver enzymes, more frequent liver fibrosis/cirrhosis (aOR=3.1 (1.1–8.2)) and primary liver cancer (aOR=6.6 (1.6–26.9)). The higher fibrosis burden was confirmed in a multinational cohort. Male sex, age ≥50 years, obesity and the presence of diabetes were associated with significant liver fibrosis. Conclusion: Our study defines the hepatobiliary phenotype of individuals with the most relevant AATD genotypes including their predisposition to liver tumours, thereby allowing evidence-based advice and individualised hepatological surveillance.